Diskresi Penggunaan Dana Cadangan (Provisional Sum) Pada Tender Pekerjaan Konstruksi Dengan Sumber Pendanaan Anggaran Pendapatan Dan Penerimaan Negara (APBN) - Herlambang, Fahreza; Rembrandt, Rembrandt; Fauzi, Wetria (Nagari Law Review, 2024)
In the construction work tender mechanism with state budget funding sources, there are no provisions or clauses relating to the use of reserve funds (provisional sum). The use and provisional sum clause can be found in the procurement of goods/services with international contract standards, for example, FIDIC contract standards and the procurement of integrated design and build work. The addition of provisional sum requirements is a discretion by Middle High Leadership Officials, in the form of adding clauses to the Special Conditions of Contract, which does not become an assessment point or point that can invalidate the Provider Selection process. If the provisional sum is not interpreted as calculating unexpected costs or other costs, then it does not conflict with the provisions for preparing own estimated price in statutory regulations and meets the Discretionary requirements as regulated in the Government Administration Law.